Tingkat Pengetahuan, Sikap, Pola Konsumsi Makanan Mengandung Zat Besi Dan Konsumsi Tablet Tambah Darah Pada Remaja - Bertalina Bertalina; Elsa Diwala (Nutrition Department, Poltekkes Kemenkes Tanjung Karang, 2025)
Anemia is one of the nutritional problems that occurs in adolescents. In 2018, anemia in Lampung Province was 11.67%, while the prevalence of anemia in Bandar Lampung City was 23.37% (Lampung Provincial Health Office, 2018). The purpose of this study was to determine the level of knowledge, attitudes, consumption patterns of foods containing iron and compliance with the consumption of iron tablets in adolescent girls. The sample in this study was 38 adolescent girls, data collection for this study used a questionnaire on knowledge, attitudes, compliance with the consumption of iron tablets and FFQ. The location of the study was carried out at SMP IT Fitrah Insani Bandar Lampung. The results showed that the majority of adolescent girls had good knowledge of anemia (55.3%), positive attitudes regarding anemia treatment (52.6%), and poor consumption patterns of foods containing iron (57.9%). In addition, it is known that only 2.6% of adolescent girls consume Iron Tablets (TTD). The government already has a program to provide iron tablets, so schools are expected to provide health media about the benefits and invitations to consume iron tablets (TTD) in the school environment. Schools can also organize joint iron tablets once a week and provide independent iron tablets. Local health centers are expected to provide motivation and education about anemia and the benefits of iron tablets to increase the effectiveness of iron tablet consumption.